Market Research Analysis for the Launch of Electric Cars in India - Raveendra Prasad, Praveen (2010)
The Indian automobile industry has come a very long way from a humble beginning to the present state where it is producing several thousands of cars every year. It is poised for a very attractive growth Almost all of the world’s leading automobile manufacturers have a significant presence in India. However despite all these, electric cars have not been very popular in India. Currently in India there is only a single automobile company ‘Mahindra Reva Electric Vehicle Company Limited’ which manufactures complete electric cars. Even with close to fifteen years of presence, the company has not been able to do good business.